Colonic metastasis from breast carcinoma detection by CESM and PET/CT: A case report. Issue 21 (May 2018) - Falco, Giuseppe; Mele, Simone; Zizzo, Maurizio; Di Grezia, Graziella; Cecinato, Paolo; Besutti, Giulia; Coiro, Saverio; Gatta, Gianluca; Vacondio, Rita; Ferrari, Guglielmo
Abstract: Introduction: Metastatic spread in invasive lobular carcinoma (ILC) of breast mainly occurs in bones, gynecological organs, peritoneum, retroperitoneum, and gastrointestinal (GI) tract. Metastases to the GI tract may arise many years after initial diagnosis and can affect the tract from the tongue to the anus, stomach being the most commonly involved site. Clinical presentations are predominantly nonspecific, and rarely asymptomatic. CEA, CA 15–3, and CA 19–9 may be informative for symptomatic patients who have had a previous history of breast cancer. Case presentation: We introduce the case of asymptomatic colonic metastasis from breast carcinoma in a 67-year-old woman followed-up for Luminal A ILC. Diagnosis was performed through positron emission tomography/computed tomography (PET/CT) scan and contrast-enhancement spectral mammography (CESM), steering endoscopist to spot the involved intestinal tract and in ruling out further dissemination in the breast parenchyma. Conclusion: In colonic metastases, tumor markers might not be totally reliable. In asymptomatic cases, clinical conditions might be underappreciated, missing local or distant recurrence. CT and PET/CT scan might be useful in diagnosing small volume diseases, and steering endoscopist toward GI metastasis originating from the breast. CESM represents a tolerable and feasible tool that rules out multicentricity and multifocality of breast localization. Moreover, particular patients could tolerate it better than magnetic resonance imaging (MRI).